Development of Assessments to Measure Students' Science Literacy Ability: Rasch Modeling Analysis - Andaresta, Ocha; Muliani, Muliani; Safriana, Safriana; Sakdiah, Halimatus; Novita, Nanda (Department of Physics Education, Universitas Mataram, 2023)
Science literacy is a demand for education in the 21st century. The ability of science literacy in Indonesia is relatively low because the questions used are not based on scientific literacy. This research aims to produce assessment products that are suitable for use, then find out the responses of teachers and students, and find out the science literacy ability of students. The method in this research is Research and development (R&D) using the Borg & Gall development model to the eighth stage. The results obtained in this study are: (1) Product feasibility results based on material experts by 78% and declared feasible, then on media experts by 87.49% and declared possible. Then, the results of the validity of question items are displayed as suitable for use with a total of 20 valid questions, item reliability 0.90 (excellent). (2) The teacher's response result of 93.5% is excellent. Then, the response of students of 88.13% was excellent. (3) The lowest science literacy ability of students is in science as a way to conduct investigations, which is 34.50%, and the highest in science as a stem of science at 72.50%.